Hubungan Kejadian Premenstrual Syndrome (PMS) Dengan Kualitas Tidur Pada Remaja Putri Di SMPN 3 Unggul Ingin Jaya Kabupaten Aceh Besar - Fauziah Fauziah; Yadi Putra; Busratul Muazinah (Jurnal Anestesi, 2023)
The growth of teenage girls change physically and psychologically. These girls tend to experience several symptoms before the menstrual phase-physical, psychological, and behavioral alteration that occur regularly during the menstrual period. The PMS symptoms that experience by teenage girls is painful cramps often accompanied by sleep quality disturbance. Poor sleep quality can affect to long-term physical disorders. This study aims to analyze the relationship between incidences of premenstrual syndrome and sleep quality among teenage girls. This study was a quantitative correlation study with a cross-sectional design. The primary data collection carried out on March 2nd-15th, 2023. The population in this study were all female students of SMPN 3 Unggul Ingin Jaya, a total of 280 students. The sampling technique used a proportional sampling technique involving 74 respondents. The Chi-Square test using univariate and bivariate statistical analysis showed the level of premenstrual syndrome among these girls experienced mild category (32.4%), moderate (37.8%), and severe (29.7%). The result also indicated that the level of sleep quality (10.8%) of respondents had good sleep quality. The rest of respondents (89.2%) had poor sleep quality. In conclusion, the result shows a relationship between PMS and sleep quality (p=0.020) of premenstrual syndrome among students at SMPN 3 Unggul Ingin Jaya, Aceh Besar. It expects that female students as respondents can utilize this study as input to enrich in-depth information if they experience premenstrual syndrome.